Sistema de ultra-som para caracterização de leite bovino - Dorabiato, Luiz Fernando (2007)
This work presents the design, development and tests of an ultrasonic milk analyzer. Milk analyzers are employed by dairy industry to evaluate the quality of acquired milk. Some of the assessed features are the fat content, solids non-fat and added water to the milk samples. These features are employed to estimate the production income of dairy products and milk adulteration. The system pumps a sample to the test cell, then the cell is warmed and the measurements are done at known temperature. Then, the system acquires the amplitude and the propagation time of the ultrasound pulse through the sample and correlates these acoustic parameters to the fat content, solids non-fat, proteins and added water in milk samples. The system showed good reproducibility, presenting low coefficient of variation (lower than 8.8%) for analysis of solid content in milk samples – fat, proteins and solids non-fat. The calibration tests presented determination coefficients between the acoustic parameters (attenuation and propagation time) and the milk components (fat content, solids non-fat, proteins and added water) higher than 97% (R2 > 0.97), with standard error of estimate lower than 1.25%, showing low dispersion of the experimental data in relation to the regression curves. To evaluate the developed prototype, comparative tests in milk samples of only one supplier were carried out using the prototype and reference equipments. In spite of the small number of samples evaluated, the maximum absolute percent errors obtained for the analysis of solid content in milk were 12.6% for fat content, 12.37% for proteins and 13.76% for solids non-fat. The percent errors obtained for the amount of added water were higher than 40%, however these errors should be reduced using a higher number of samples/suppliers during the final calibration/evaluation process of the developed prototype. The preliminary results allow to conclude that the ultrasound system developed is adequate to quantify the main components of bovine milk.